All Is Data - Barney G. Glaser (Grounded Theory Review: An International Journal, 2007)
All is data” is a well known Glaser dictum. What does it mean? It means that exactly what is going on in the research scene is the data, what ever the source, whether interview, observations, documents. It is not just what is being, how it is being and the conditions of its being told, but all the data surrounding what is being told. It means what is going on has to be figured out exactly what it is for conceptualization, NOT description. Data is always as good as far as it goes, and there is always more to keep correcting the categories with more relevant properties.